Post-Pandemic Valuation Anomaly: Why Current Ratio Failure To Mediate Roa And Der On Pbv In The Chemical Sector On The Idx - Sukirno Sukirno; Rindi Wahyuni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study reveals the failure of the Current Ratio (CR) to mediate the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Price to Book Value (PBV) in 12 chemical companies on the Indonesian Stock Exchange (IDX) for the period 2020-2023 (n=48, post-outlier n=31). Using path analysis, the Sobel test, and a robustness check (SPSS 27) after log transformation, the model meets the classical assumptions (KS p=0.200, VIF<3, DW=2.33). Main findings: ROA (β=8.438, p<0.01) and DER (β=1.043, p<0.01) have a significant positive effect directly on PBV (R² adj=64.0%); DER has a significant negative effect on CR (β=-4.917, p<0.01). However, CR is insignificant on PBV (β=0.005, p=0.878), resulting in insignificant mediation (indirect ROA=0.007, DER=-0.017; Sobel z<1.96). Fixed effects confirm robustness. The results supportsignalling theory(ROA efficiency signal) andtrade-off theory(optimal DER), but reject contingency mediation in the high liquidity chemical sector post-COVID.Managerial implications: Prioritize ROA optimization (>5%) over excess liquidity; investors weigh profitability higher than balance sheet liquidity in chemical valuations.